Distributed Computing 23rd International Symposium, DISC 2009, Elche, Spain, September 23-25, 2009. Proceedings - Keidar, Idit. (Lecture Notes in Computer Science, 2009)
This book constitutes the refereed proceedings of the 23nd International Symposium on Distributed Computing, DISC 2009, held in Elche, Spain, in September 2009. The 33 revised full papers, selected from 121 submissions, are presented together with 15 brief announcements of ongoing works; all of them were carefully reviewed and selected for inclusion in the book. The papers address all aspects of distributed computing, and were organized in topical sections on Michel Raynal and Shmuel Zaks 60th birthday symposium, award nominees, transactional memory, shared memory, distributed and local graph algorithms, modeling issues, game theory, failure detectors, from theory to practice, graph algorithms and routing, consensus and byzantine agreement and radio networks.